Analisis Dampak Perubahan Iklim dan Pola Angin Pada Lingkungan Global - Anggraeni, Nuril Martha; ., Sudarti; ., Yushardi (Jurnal Pendidikan, Sains Dan Teknologi, 2023)
Climate change and wind patterns have become the focus of global attention due to their damaging impacts on the environment and ecosystems around the world. This study aims to analyze the impacts of climate change, including global temperature rise and changes in extreme weather patterns, and their implications for changes in global wind patterns. The data analysis method is based on a literature study on the interaction between climate change and wind patterns, including their effects on natural cycles and environmental sustainability. The results show that climate change induced by human activities, such as increased greenhouse gas emissions, has led to an increase in global average temperatures. This has resulted in drastic changes to wind patterns in many parts of the world, including an increase in extreme weather events such as tropical storms, floods and extensive droughts. These impacts damage terrestrial and marine ecosystems, disrupt the balance of nature, and threaten the sustainability of natural resources. The effects of climate change and wind patterns are not only limited to environmental aspects, but also affect the economic sector and human well-being. With the increasing risk of natural disasters and environmental damage, mitigation and adaptation efforts need to be enhanced through the implementation of sustainable policies, reduction of greenhouse gas emissions, and development of environmentally friendly technologies. Increasing global awareness of the importance of collective action to address climate change and wind patterns is key to securing the future of the global environment and ecosystem sustainability.